Molecular mechanisms of photosensitization induced by drugs XIV: Two different behaviours in the photochemistry and photosensitization of antibacterials containing a fluoroquinolone like chromophore - G. De Guidi; S. Giuffrida; S. Monti; P. S. Pisu; S. Sortino; L. L. Costanzo (International Journal of Photoenergy)
This paper deals with the photosensitizing activity of FLQs towards two different biosubstrates, membrane and DNA. The in vitro phototoxic activity of these drugs vs. DNA presents peculiar features with respect to that vs. membranes, probably due to a specific binding of the drugs to the double helix and to the operativeness of different photosensitization mechanisms with the two types of biosubstrates. A description of the UVA photochemistry and the photosensitizing properties of two significant examples in the FLQ family is reported. The investigated compounds are Enoxacin, 1-ethyl-6-fluoro-1,4-dihydro-4- oxo-7-[1-piperazinyl]-1,8-naphtyridine-3-carboxilic acid and Rufloxacin, 9-fluoro-2,3-dihydro-10-4´-methyl- 1´-piperazinyl-7-oxo-7H-pyrido[1,2,3−de]-1,4-benzothiazine-6-carboxylic acid.